1996
DOI: 10.1111/j.1432-1033.1996.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Method to Predict Mitochondrially Imported Proteins and their Targeting Sequences

Abstract: Most of the proteins that are used in mitochondria are imported through the double membrane of the organelle. The information that guides the protein to mitochondria is contained in its sequence and structure, although no direct evidence can be obtained. In this article, discriminant analysis has been performed with 47 parameters and a large set of mitochondrial proteins extracted from the SwissProt database. A computational method that facilitates the analysis and objective prediction of mitochondrially impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
1,215
1
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,541 publications
(1,242 citation statements)
references
References 37 publications
21
1,215
1
5
Order By: Relevance
“…Prediction programs suggested that this could be an organellar targeting sequence. MitoProt (Claros and Vincens 1996), searching for putative mitochondrial targeting sequences, strongly predicted (score of 0.97) a 53-amino acid N-terminal targeting peptide. ChloroP (Emanuelsson et al 1999), searching for chloroplast targeting sequences, predicted (score of 0.56) a 34-amino acid N-terminal targeting peptide.…”
Section: Organellar Targetingmentioning
confidence: 99%
“…Prediction programs suggested that this could be an organellar targeting sequence. MitoProt (Claros and Vincens 1996), searching for putative mitochondrial targeting sequences, strongly predicted (score of 0.97) a 53-amino acid N-terminal targeting peptide. ChloroP (Emanuelsson et al 1999), searching for chloroplast targeting sequences, predicted (score of 0.56) a 34-amino acid N-terminal targeting peptide.…”
Section: Organellar Targetingmentioning
confidence: 99%
“…Mitochondrial localization is predicted for several NOCT orthologs. PSORTII [101,102], TargetP [103], and MitoProt [104] all predict mitochondrial localization of X. tropicalis, R. norvegicus, H. sapiens, M. musculus , and D. rerio NOCTA. TargetP and MitoProt predictions indicate that D. rerio NOCTB is likely to be mitochondrial; however, this conflicts with the nuclear localization predicted by PSORTII.…”
Section: Is Noct Activity Spatially Restricted?mentioning
confidence: 99%
“…TargetP and MitoProt predictions indicate that D. rerio NOCTB is likely to be mitochondrial; however, this conflicts with the nuclear localization predicted by PSORTII. Neither TargetP nor MitoProt identify D. melanogaster or X. laevis NOCT as mitochondrial [103,104]. Although useful in predicting possible NOCT functions, these programs do not account for shuttling among subcellular compartments.…”
Section: Is Noct Activity Spatially Restricted?mentioning
confidence: 99%
“…The putative mitochondrial signal of PfCYP32 was further investigated since mitochondrial proteins of P. falciparum are very different from human mitochondrial proteins, making them attractive potential drug targets [33]. It was scanned for mitochondrial sequences with MitoProt [34], PlasMit [35] and PFM Pred [36]. All algorithms predicted PfCYP32 to be a mitochondrial protein.…”
Section: Data Mining Alignments and Annotated Datamentioning
confidence: 99%